Investigation of structural and physical properties of Eu3+ ions substituted Ni0.4Cu0.2Zn0.4Fe2O4 spinel ferrite nanoparticles prepared via sonochemical approach - Slimani, Y.; Unal, B.; Almessiere, M.A.; Korkmaz, A. Demir; Shirsath, Sagar E.; Yasin, Ghulam; Trukhanov, A.V.; Baykal, A. (Results in physics, 2020)
•Ni0.4Cu0.2Zn0.4Fe2−xEuxO4 (x = 0.00 – 0.10) nanoparticles were synthesized via ultrasonic irradiation.•Optical band gap energies belong to semiconducting system.•Superparamagnetic property at RT and soft ferromagnetic nature below TB are noticed.•A decreasing trend in the magnetization was observed with Eu3+ substitution.•Dielectric and electrical properties Ni0.4Cu0.2Zn0.4Fe2−xEuxO4 NPs were investigated. Green and facile process for Ni0.4Cu0.2Zn0.4Fe2−xEuxO4 (x = 0.00–0.10) spinel ferrite nanoparticles (SNPs) prepared via ultrasonic irradiation (without any post annealing process) has been deeply investigated. The influence of Eu3+ substitutions on the structure, morphological, optical, magnetic, electrical and dielectric traits of NiCuZn SNPs was assessed. Tauc plots revealed direct optical band gaps in a very tight interval of 1.86–1.90 eV. Magnetization measurements exposed a superparamagnetic behavior at room temperature and below the blocking temperature (TB) a superparamagnetic-ferromagnetic transition was noticed. The saturation magnetization (Ms) value is highest for pure Ni0.4Cu0.2Zn0.4Fe2O4 (i.e. x = 0.00) SNP with Ms ~ 58.9 emu/g at room temperature. The saturation magnetization (Ms) declines with rising Eu3+ substituting content. AC conductivity decreases as a function of exponent power base law. Maximum variation in dc conductivity is observed to be around the substitution ratio of x = 0.02. It is found that activation energy is highly dependent on both Eu ions substitution ratios and temperature ranges. The frequency dependence of dielectric functions is explained by Koop's models based on Maxwell-Wagner theory.